Imperial Affects : Sensational Melodrama and the Attractions of American Cinema - Eagle, Jonna, 1968- (Book collections on Project MUSE., 2017)
"In American culture and history, a feeling of national identity and belonging have often derived from a sense of injury, vulnerability, and loss. Sympathy and aggression operate as twinned affects in such contexts, with representations of an assaulted national body animating identification with nationalist violence and its agents. In Imperial Affects, Jonna Eagle turns to the workings of American cinema to understand the power and persistence of these conjunctions, tracing the shifting dynamics of action and pathos as they structure representations of imperialist motion and violence across the twentieth century"--